2002
DOI: 10.1002/nme.543
|View full text |Cite
|
Sign up to set email alerts
|

A continuum sensitivity method for finite thermo‐inelastic deformations with applications to the design of hot forming processes

Abstract: SUMMARYA computational framework is presented to evaluate the shape as well as non-shape (parameter) sensitivity of ÿnite thermo-inelastic deformations using the continuum sensitivity method (CSM). Weak sensitivity equations are developed for the large thermo-mechanical deformation of hyperelastic thermoviscoplastic materials that are consistent with the kinematic, constitutive, contact and thermal analyses used in the solution of the direct deformation problem. The sensitivities are deÿned in a rigorous sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It has been shown that the deformation sensitivity response does not explicitly depend on the history of the temperature sensitivity but is dependent only on the instantaneous temperature sensitivity response h nþ1 (Ganapathysubramanian and Zabaras, 2002). The solution of the sensitivity subproblem is advanced within the incremental solution scheme by integrating the evolution equations for the sensitivity of the plastic and thermal deformation gradients, the evolution equation for the sensitivity of the state variable s and the grain size L. As part of this sub-problem, the linear relationship between T and ½F ; h at time t nþ1 is computed.…”
Section: Sensitivity Constitutive Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the deformation sensitivity response does not explicitly depend on the history of the temperature sensitivity but is dependent only on the instantaneous temperature sensitivity response h nþ1 (Ganapathysubramanian and Zabaras, 2002). The solution of the sensitivity subproblem is advanced within the incremental solution scheme by integrating the evolution equations for the sensitivity of the plastic and thermal deformation gradients, the evolution equation for the sensitivity of the state variable s and the grain size L. As part of this sub-problem, the linear relationship between T and ½F ; h at time t nþ1 is computed.…”
Section: Sensitivity Constitutive Problemmentioning
confidence: 99%
“…The sensitivity thermal problem and the contact sensitivity problems are dealt the same way as described in Ganapathysubramanian and Zabaras (2002). The next section deals with numerical analysis and involves the comparison of the direct solution with results available experimentally.…”
Section: Calculation Of the Linear Relation Betweenmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al [4] have proposed to use an IGP to estimate the shape of frost growth on an evaporating tube by using temperature readings. Ganapathysubramanian et al [5] have presented a framework to evaluate the shape sensitivity of finite thermo-inelastic deformations and have applied the method to the design of open-and closed-die forging processes.…”
Section: Introductionmentioning
confidence: 99%